2018
DOI: 10.5604/01.3001.0012.4700
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Time Effects of Group Therapy Intervention on Marriage Communication Between Fluent and Non-Fluent Aphasic Patients and Their Spouses: Who Benefits the Most?

Abstract: Our study aims to assess the long-time effects of group therapy intervention on marriage communication between fluent and non-fluent aphasic patients and their spouses. From the initial cohort of 150 couples four experimental groups have been selected, each comprising 20 subjects: (1) patients with fluent aphasia (FAP) (2) patients with fluent aphasia spouses (FAPS) (3) patients with non-fluent aphasia (NFAP) (4) patients with non-fluent aphasia spouses (NFAPS). All aphasic patients had mild or moderate flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…40 Aside from the largest study with 349 caregivers, 24 there were 5 studies with over 100 caregivers or dyads 19,26,28,33,34 ; however, 2 of the studies reported findings using the same sample. 33,34…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Aside from the largest study with 349 caregivers, 24 there were 5 studies with over 100 caregivers or dyads 19,26,28,33,34 ; however, 2 of the studies reported findings using the same sample. 33,34…”
Section: Resultsmentioning
confidence: 99%
“…40 Aside from the largest study with 349 caregivers, 24 there were 5 studies with over 100 caregivers or dyads 19,26,28,33,34 ; however, 2 of the studies reported findings using the same sample. 33,34 Interventions Detailed descriptions of content and procedures for the intervention and control conditions were provided in each of the 18 articles. Only 1 study reported blinding of participants to the type of intervention they received.…”
Section: Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining nine studies were categorized as experimental interventions (Attard et al, 2018; Karahan et al, 2014; Kim et al, 2012; Mackenzie et al, 2012; Malini, 2015; Mores et al, 2018; Orłowska et al, 2018; Saldert et al, 2015; Song et al, 2011). Most of these interventions were created for couples and families but did not have clear descriptions of or strong foundations for their couple or family intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these interventions were created for couples and families but did not have clear descriptions of or strong foundations for their couple or family intervention. Whether possibly efficacious or experimental, the studies that comprised high family inclusion ( n = 13; see Table S2g) revealed improved family functioning (Bishop et al, 2014; Cheng et al, 2018), less criticism (Bishop et al, 2014), better social support (Cheng et al, 2018; Ostwald et al, 2014), lower caregiver burden (Kim et al, 2012; Mei et al, 2018; Mores et al, 2018), more frequent sexual activity (Song et al, 2011), and improved communication (Orłowska et al, 2018; Saldert et al, 2015) and family strengths (Malini, 2015). Even those with moderate family inclusion ( n = 6; see Table S2g) showed at least some positive results for both stroke survivors and caregiver/family members, including psychological benefits (e.g., reduced depression, anxiety, caregiver burden/stress, or improved positive coping skills) and physical health improvements (e.g., health status).…”
Section: Resultsmentioning
confidence: 99%